Derecho indígena en el Amazonas: justicia Múrui (2016)
The present socio legal investigation article was development from field researches in several Múrui indigenous communities in Colombian Amazon Region; in the researches was established like objective to investigate the application of Múrui legal system according to the use and customs, and the role that plays the Múrui worldview on their own justice notion. This article shows oppositions in the relation between the ordinary jurisdiction and the indigenous Múrui special jurisdiction, for the recognition of legitimacy and autonomy in the procedures to resolve conflicts and to apply the justice.